Estimated maturity status and perceptions of adult autonomy support in youth soccer players - Cumming, S. P.; Battista, R. A.; Standage, M.; Ewing, M. E.; Malina, R. M. (Journal of Sports Sciences, 2007)
In this study, we examined the relations between biological maturity status, body mass index, age, and perceptions of adult autonomy support in the context of youth soccer. A total of 70 female and 43 male soccer players, aged 9 - 15 years, completed three adult-specific versions (i.e. mother, father, coach) of the perceived autonomy support subscale from the Interpersonal Style Scale. The participants' percent predicted adult stature was used as an estimate of biological maturity status. Multiple linear regression analyses revealed that advanced maturity status in male players predicted lower perceptions of autonomy support from the coach. Maturity status was unrelated to perceptions of autonomy support from the coach in female soccer players, and paternal and maternal autonomy support in male and female players. Age and body mass index were unrelated to perceptions of adult (i.e. coach, mother, father) autonomy support in male and female players.